2004
DOI: 10.1590/s0034-89102004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Doenças respiratórias agudas em serviços de saúde entre 1996 e 2001, Fortaleza, CE

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…A similar result was also reported in a study in Ceará, with more cases of respiratory diseases reported by health services from May to June 28 .…”
Section: Specificationsupporting
confidence: 89%
“…A similar result was also reported in a study in Ceará, with more cases of respiratory diseases reported by health services from May to June 28 .…”
Section: Specificationsupporting
confidence: 89%
“…Alguns estudos têm mostrado a relação entre a variação sazonal e as proporções de atendimentos ambulatoriais por doenças respiratórias (DR), assim como a ocorrência de internações hospitalares [1][2][3][4][5] .…”
Section: Introductionunclassified
“…Acute respiratory infection is one of the 5 main causes of death in children under 5 years of age in developing countries. 1 About 40% of children needing medical attention suffer from acute respiratory infection 2 , where community-acquired pneumonia is the most severe, causing 80% of deaths 3,4 . In Brazil, acute lung diseases are responsible for 11% of deaths in children under 1 year old and 13% in the age group between 1 and 4 years 5 .…”
Section: Introductionmentioning
confidence: 99%